Application of aqueous biphasic systems for the separation of amino acids and proteins - Belchior, Diana Cléssia Vieira (2020)
This work was focused on the application of aqueous biphasic systems (ABS) composed of tetraalkylammonium-based ionic liquids (ILs) aiming at developing more effective separation processes for amino acids and proteins. It is first demonstrated the impact of the alkyl chain length of the IL anion on the ABS formation and on these systems performance to extract amino acids, where odd-even effects have been identified. ILs composed of anions with even alkyl chains exhibit a slightly higher capacity to form ABS, whereas systems formed by ILs with anions comprising odd alkyl chains lead to slightly higher amino acid partition coefficients. After addressing the ILbased ABS performance to extract amino acids, it is then demonstrated the influence of the IL chemical structure and the effect of pH on the extraction and recovery yield of ovalbumin and lysozyme, two proteins present in egg white. At pH 7, the complete extraction and recovery of lysozyme to the ILrich phase was achieved with all systems; however, low ovalbumin recovery yields were obtained with ABS formed by ILs with longer alkyl side chains. Molecular docking studies revealed that ILs that preferentially establish hydrophobic interactions with these proteins lead to their aggregation and lower recovery yields. The recovery of the proteins (up to 99%) from the ILrich phase by precipitation with ice-cold ethanol was also demonstrated. Finally, polymer-salt ABS comprising ILs as adjuvants (at 5 wt%) were investigated to tailor the phases polarities and these systems selectivity to simultaneously separate ovalbumin and lysozyme. Studies with commercial proteins and directly from egg white were carried out. With the systems in which no IL was added it was observed a preferential partition of ovalbumin to the polymer-rich phase, which contains the IL, whereas lysozyme tends to precipitate at the interphase. A similar trend was observed when applying the same systems to separate both proteins from egg white. However, when ILs are added, the ovalbumin and lysozyme preferentially partition to the salt-rich and PEG-rich phases, respectively, while avoiding the precipitation of the latter protein. Nevertheless, when the same systems are applied to egg white, the same behavior was not observed, indicating that a more complex phenomenon occurs due to the presence of other proteins in egg white. Although further research on the viability of some of the studied ILs and systems is still required, the results presented in this work disclose the relevance of ABS comprising ILs in the development of efficient separation processes for amino acids and proteins.